Effects of Dissolved Organic Matter on the Release of Soluble Phosphorus and Fluoride Ion from Phosphate Ore - Fengjiao Zhang; Huaying Liu; Yanqiong Ma; Yingjie Li; Cheng Tie; Qilin Zhao (Separations, 2023)
Unreasonable storage of phosphate ore is becoming an important pathway causing phosphate pollution in the surrounding aquatic environment. However, there is little research on the influence of dissolved organic matter (DOM) in water on the fate of phosphate ore. Here, we collected phosphate ores from two phosphate mines along the coast of Tanglang River and studied the effects of DOM concentrations and pH on the release of soluble active phosphorus (SRP) and fluoride ion (F−) from phosphate ores using humic acid (HA) as the representative of DOM. Based on the analysis of ZP, FTIR, XPS, and SEM, the influence mechanism of HA was revealed. The results showed that HA efficiently promoted the release of SRP and F− from phosphate ore. With decreasing pH, the P release increased in both water and HA solutions in general. The beneficial influence of HA on the release of SRP and F− from phosphate ore was ascribed to the introduction of oxygen-containing functional groups by HA, which altered the surface properties and enhanced the dispersion stability of phosphate ore. These findings provided new insights into the dispersion behavior of phosphate ore, which is helpful in promoting the pollution control and management strategy of phosphate ore.